CHARACTERISTIC OF OVARIAN AND ESTRADIOL CONCENTRATIONS IN THE FOLLICULAR FLUID OF SLAUGHTERED ACEH CATTLE - Mulyadi Adam; Gholib Gholib; Hafizuddin Hafizuddin; Rumi Sahara Zamzami; Muhammad Bahi (Jurnal Kedokteran Hewan, 2019)
The objective of this study was to characterize the morphology of ovary from slaughtered Aceh cow and measuring the concentration of estradiol in the follicular fluid to examine the potential utilizing for in-vitro fertilization (IVF) development in Aceh cattle. In total, 30 pairs of ovaries were collected from 30 Aceh cattle slaughtered at Banda Aceh abattoir. Morphological characteristics of ovaries observed were the size of ovaries, weight of ovaries, number of follicles, the diameter of follicles, corpus luteal (CL), and volume of follicular fluid. The follicular fluid was aspirated using a disposable syringe and analyzed the estradiol concentrations using enzyme-linked immunosorbent assay (ELISA). The follicles were grouped into 3 categories based on the diameter (Ø) of follicles: small follicles (Ø 1 - 5 mm), medium follicles (Ø 5 - 8 mm), and large follicles (Ø 8 mm). The morphological characteristic of ovaries varied between right and left ovaries in which right ovaries showed bigger size and weight compared to the left ovaries (P0.05), whereas the number of follicles and follicular fluid did not significantly different (P0.05). The concentrations of estradiol in follicular fluid of large and medium follicles were significantly higher compared to small follicles (P0.05), whereas the concentration of estradiol between large and medium follicles, did not significant different (P0.05). In conclusion, the follicles from abattoir can be used as potential oocytes resources to support IVF development for Aceh cattle in the future. The follicular fluid provided from these follicles can be an alternative for in vitro maturation media of oocytes due to containing high estradiol concentrations.